Identification and Expression of Immunogenic Proteins of a Disease-Associated Marine Turtle Herpesvirus - Coberley, Sadie S. (American Society for Microbiology, 2002)
Herpesviruses are associated with several diseases of marine turtles, including lung-eye-trachea disease (LETD) and fibropapillomatosis. Two approaches were used to identify immunodominant antigens of LETV, the LETD-associated herpesvirus. The first approach targeted glycoprotein B, which is known to be immunogenic and neutralizing in other species. The second strategy identified LETV proteins recognized on Western blots by antibodies in immune green turtle plasma. A 38-kDa protein was resolved by two-dimensional gel electrophoresis, sequenced, and identified as a scaffolding protein encoded by the overlapping open reading frames of UL26 and UL26.5. Glycoprotein B and the scaffolding protein were cloned and expressed in Escherichia coli. The expressed proteins were recognized on Western blots by antibodies in immune green turtle plasma. Phylogenetic studies based on UL26, DNA polymerase, and glycoprotein B revealed that LETV clusters with the alphaherpesviruses.